Study of the Camshaft Feed of an Internal Combustion Engine - Huseynov, A.G.; Kerimov, A.F. (Herald of Azerbaijan Engineering Academy, 2025)
The article examines the factors affecting the wear of camshafts of internal combustion engines during operation, provides information on measures to reduce and eliminate them, and discusses the measurement technique and the results of wear of the camshaft cam, which is the object of the study. As is known, the camshaft, as one of the main parts of the gas distribution mechanism, has a direct impact on the synchronous operation of the engine, fuel consumption and environmental pollution. Its failure is considered an operation that requires an expensive repair process. Studying the wear of the camshaft is important for targeted determination of the volume of strengthening and restoration work, as well as for the correct determination of the cause of its failure.